Effects of anti-epileptic drugs on spreading depolarization-induced epileptiform activity in mouse hippocampal slices - Lin, Ching-Huei (Sci Rep, 2017)
Epilepsy and spreading depolarization (SD) are both episodic brain disorders and often exist together in the same individual. In CA1 pyramidal neurons of mouse hippocampal slices, induction of SD evoked epileptiform activities, including the ictal-like bursts, which occurred during the repolarizing phase of SD, and the subsequent generation of paroxysmal depolarization shifts (PDSs), which are characterized by mild depolarization plateau with overriding spikes. The duration of the ictal-like activity was correlated with both the recovery time and the depolarization potential of SD, whereas the parameters of PDSs were not significantly correlated with the parameters of SD. Moreover, we systematically evaluated the effects of multiple anti-epileptic drugs (AEDs) on SD-induced epileptiform activity. Among the drugs that are known to inhibit voltage-gated sodium channels, carbamazepine, phenytoin, valproate, lamotrigine, and zonisamide reduced the frequency of PDSs and the overriding firing bursts in 20–25 min after the induction of SD. The GABA uptake inhibitor tiagabine exhibited moderate effects and partially limited the incidence of PDSs after SD. AEDs including gabapentin, levetiracetam, ethosuximide, felbamate, and vigabatrin, had no significant effect on SD-induced epileptic activity. Taken together, these results demonstrate the effects of AEDs on SD and the related epileptiform activity at the cellular level.